2022
DOI: 10.3389/fendo.2022.878634
|View full text |Cite|
|
Sign up to set email alerts
|

The Silent Epidemic of Diabetic Ketoacidosis at Diagnosis of Type 1 Diabetes in Children and Adolescents in Italy During the COVID-19 Pandemic in 2020

Abstract: Aim/HypothesisTo compare the frequency of diabetic ketoacidosis (DKA) at diagnosis of type 1 diabetes in Italy during the COVID-19 pandemic in 2020 with the frequency of DKA during 2017-2019.MethodsForty-seven pediatric diabetes centers caring for >90% of young people with diabetes in Italy recruited 4,237 newly diagnosed children with type 1 diabetes between 2017 and 2020 in a longitudinal study. Four subperiods in 2020 were defined based on government-imposed containment measures for COVID-19, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
(32 reference statements)
2
5
0
Order By: Relevance
“…Interestingly, prevalence of severe DKA in our center was relatively higher in comparison to other Italian studies [ 14 ] and to other developed countries [ 15 17 ], but in accordance with recent epidemiologic data from Southern Italy [ 18 , 19 ]. Our analysis also showed an apparent increase in severity of DKA during the period 2020–2021.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, prevalence of severe DKA in our center was relatively higher in comparison to other Italian studies [ 14 ] and to other developed countries [ 15 17 ], but in accordance with recent epidemiologic data from Southern Italy [ 18 , 19 ]. Our analysis also showed an apparent increase in severity of DKA during the period 2020–2021.…”
Section: Discussionsupporting
confidence: 92%
“…Islet cell damage may occur without an activation of the immune system. [ 111 ]. In fact, in a small study conducted in the UK among children with newly diagnosed T1DM, SARS-CoV-2 was detected by polymerase chain reaction (PCR) in 2/21 and SARS CoV-2 antibodies in 3/16 children tested.…”
Section: Type 1 Diabetes Mellitusmentioning
confidence: 99%
“…In fact, it is urgent to find effective drugs for pneumonia treatment. 19 Interestingly, this research revealed that UA induced protective autophagy to alleviate inflammation, oxidative stress, and endoplasmic reticulum stress in pediatric pneumonia. Pneumonia results in destruction of lung tissues, neutrophil infiltration, and release of pro-inflammatory cytokines, including TNF-α, IL-1β, and IL-6.…”
Section: Discussionmentioning
confidence: 93%